Structural analysis and measurement invariance of MBI-GS in peruvian workers - Fernández-Arata, Manuel (2015)
The measurement of burnout has evolved into the creation of various tools and models. The Maslach Burnout Inventory - General Survey (MBI-GS) is one of these instruments used to measure three definitional constructs of burnout: (1) emotional exhaustion, (2) professional efficiency, and (3) indifference. It was created for a wide range of occupations, but its latent structure and invariance of measurement in Latin America has rarely been verified. The present study analyzes the latent structure and the invariance of measurement of MBI-GS in a sample of 940 Peruvian workers in various occupations. The methodology of structural equations was applied through the confirmatory factor analysis, as well as the invariance of measurement between men and women, imposing restrictions successively more strict. The results satisfactorily verified the structure of three-dimensional latent MBI-GS, and the invariance of its parameters between men and women. The implications of the results are discussed.